Infant Feeding Practices and Analysis Of Factors Affecting Exclusive Breastfeeding - Nisman, Wenny Artanty; Aryas, Dea; Ratnasari, Evi; Widya, Melinda; Yonanta, Nevira; Rahmasari, Salma; Annisa, Varianti Novia (Jurnal Keperawatan Soedirman, 2021)
The coverage rate of exclusive breastfeeding in Indonesia is still low despite its ability to affect a baby's health status and ability to survive. In 2017, only 35.73% of babies in Indonesia received exclusive breastfeeding for up to 6 months. This study aims to determine infant feeding practices and identify the factors that influence the practice of exclusive breastfeeding in Yogyakarta. This is a descriptive analysis study with a cross-sectional approach. The instruments that have been used in this study were the demographic data questionnaire, the Iowa Infant Feeding Attitude Scale (IIFAS) questionnaire, and the Breastfeeding Self Efficacy Scale-Short Form (BSES-SF) questionnaire. A total of 421 mothers were involved in this study and the research was conducted between June 2019 to April 2020 in Sleman Regency, Yogyakarta, Indonesia. Correlation data analysis was performed using chi-square and point biserial correlation and the multivariate analysis used logistic regression. Infant feeding practice was high with 82.4% of infants receiving exclusive breastfeeding. It was found that employment status, knowledge, mothersâ€™ attitudes, and self-efficacy about breastfeeding have significant correlations with exclusive breastfeeding. Employment status, knowledge, mothersâ€™ attitudes, and self-efficacy about breastfeeding are factors that can encourage exclusive breastfeeding.Â